Clinical characterization of immunocompetent patients with Scedosporium detected in respiratory samples: A case series - Yasuhiro Ito; Seiichi Miwa; Akira Watanabe; Masahiro Shirai (Respiratory Medicine Case Reports)
Although Scedosporium is increasingly recognized in pulmonary infections, the optimal management of immunocompetent patients with Scedosporium detected in respiratory samples is poorly understood. This study aimed to characterize the clinical features of immunocompetent patients with Scedosporium detected in respiratory specimens. We retrospectively reviewed cases from 2014 to 2022 at our hospital. Eight elderly, immunocompetent female patients were identified, all presenting with bronchiectasis on chest imaging. Notably, seven (87.5 %) had a history of pulmonary Mycobacterium avium complex (MAC) disease. Based on their clinical courses, seven patients were classified as having colonization. One patient, diagnosed with infection, was treated with voriconazole, and her clinical symptoms stabilized without negative conversion of sputum cultures. Our findings suggest that bronchiectasis, particularly when linked with pulmonary MAC disease, may serve as an important underlying condition for Scedosporium colonization or infection in immunocompetent individuals. In the majority of cases, Scedosporium is indicative of colonization. However, distinguishing between colonization and infection remains a critical challenge for respiratory physicians.